Healthcare students support opt-out organ donation for practical and moral reasons - Qian, Long (Journal of medical ethics, 2022)
Background and purpose Changes to deceased organ donation policy in the USA, including opt-out and priority systems, have been proposed to increase registration and donation rates. To study attitudes towards such policies, we surveyed healthcare students to assess support for opt-out and priority systems and reasons for support or opposition. Methods We investigated associations with supporting opt-out, including organ donation knowledge, altruism, trust in the healthcare system, prioritising autonomy and participants’ evaluation of the moral severity of incorrectly assuming consent in opt-in systems (‘opt-in error’) or opt-out systems (‘opt-out error’), by conducting an online survey among healthcare students at a large academic institution. Results Of 523 respondents, 86% supported opt-out, including 53% who strongly supported the policy. The most popular reason for supporting opt-out was the potential for increased donation rates, followed by convenience for those not registered but willing to donate. The most popular reason for opposing opt-out was the belief that presuming consent is morally wrong. Those strongly supporting opt-out viewed the opt-in error as more morally unacceptable, and had higher knowledge and altruism scores. Those opposing opt-out viewed the opt-out error as more unacceptable, and had higher autonomy scores. 48% of respondents supported priority within opt-in systems; 31% supported priority in opt-out. Conclusions There is strong support for opt-out organ donation among healthcare students, influenced by both practical and moral considerations.